2007
DOI: 10.1007/s00425-007-0485-3
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation regulates the glycosylation of the reversibly glycosylated polypeptide

Abstract: Reversible glycosylated polypeptides (RGPs) are highly conserved plant-specific proteins, which can perform self-glycosylation. These proteins have been shown essential in plants yet its precise function remains unknown. In order to understand the function of this self-glycosylating polypeptide, it is important to establish what factors are involved in the regulation of the RGP activity. Here we show that incubation at high ionic strength produced a high self-glycosylation level and a high glycosylation revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…In support of this, C1RGPs also localize to developing cell plates during cell division (Zavaliev et al, 2010); a process that also requires CalS-dependent callose deposition (Thiele et al, 2009). Alternatively, accumulation of C1RGPs in the PM facing the PD cytoplasmic sleeve may form large homo-multimeric protein complexes (~400 kDa) (De Pino et al, 2007), physically obstructing the PD pore and hence blocking symplastic connectivity (Sagi et al, 2005; Zavaliev et al, 2010). …”
Section: Developmental Modulation Of Pd Connectivity: Callose Turnovementioning
confidence: 99%
“…In support of this, C1RGPs also localize to developing cell plates during cell division (Zavaliev et al, 2010); a process that also requires CalS-dependent callose deposition (Thiele et al, 2009). Alternatively, accumulation of C1RGPs in the PM facing the PD cytoplasmic sleeve may form large homo-multimeric protein complexes (~400 kDa) (De Pino et al, 2007), physically obstructing the PD pore and hence blocking symplastic connectivity (Sagi et al, 2005; Zavaliev et al, 2010). …”
Section: Developmental Modulation Of Pd Connectivity: Callose Turnovementioning
confidence: 99%
“…RGPs from various plant species have been demonstrated to form homoprotein or heteroprotein complexes (Langeveld et al, 2002;Drakakaki et al, 2006;De Pino et al, 2007). To investigate the Arabidopsis RGPs regarding protein complex formation, composition, and enzymatic activities, we stably expressed the corresponding proteins in Arabidopsis as translational hemagglutinin (HA) tag fusions under the control of their native promoters.…”
Section: Protein Complex Formationmentioning
confidence: 99%
“…The mutases belong to a small gene family that encodes the previously named Reversibly Glycosylated Proteins (RGPs), which is unrelated to the UDPgalactomutases present in some microorganisms. Until now, numerous RGPs from diverse plant species have been isolated and demonstrated to be reversibly glycosylated by nucleotide sugars such as UDP-Glc, UDP-Xyl, and UDP-Gal (Dhugga et al, 1991;Langeveld et al, 2002;De Pino et al, 2007;Konishi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast two-hybrid screening showed that the wheat RGPs form homomultimers or heteromultimers with RGPs from both subgroups. De Pino et al (2007) also observed oligomerization of potato (Solanum tuberosum) RGPs at low ionic strength of buffers and suggested that glycosylation favored oligomerization. Rautengarten et al (2011) extended these results to show that oligomeric complexes pulled down by hemagglutinin tags contain RGP1, RGP2, and RGP5 and exhibit mutase activity.…”
Section: The Mur5 Mutation Impairs Protein Stability and The Extent Omentioning
confidence: 91%